2020
DOI: 10.35848/1347-4065/abc924
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature reliability of integrated circuit based on 4H-SiC MOSFET with Ni/Nb ohmic contacts for harsh environment applications

Abstract: The high-temperature reliability of integrated circuit based on 4H-SiC MOSFET with Ni/Nb ohmic contacts was investigated at 400 °C in N2 ambient. The results showed that the single stage amplifier remained a stable voltage gain after 100 h of aging at 400 °C. Based on the transfer length method, the Ni/Nb/n-type 4H-SiC ohmic contact exhibited the excellent stability after being aged at 400 °C for 100 h. Whereas, the stability of electrical characteristics indicated that the 4H-SiC MOSFET also exhibited a good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…ilicon carbide (SiC) is a promising material for power and harsh environment devices owing to its superior material properties, including wide bandgap, high critical electric field, and high thermal conductivity. [1][2][3][4] SiC MOSFETs are recognized as the next-generation high-efficiency power devices and have already been commercially utilized. 5) Another promising application using SiC MOSFETs is SiC CMOS ICs.…”
mentioning
confidence: 99%
“…ilicon carbide (SiC) is a promising material for power and harsh environment devices owing to its superior material properties, including wide bandgap, high critical electric field, and high thermal conductivity. [1][2][3][4] SiC MOSFETs are recognized as the next-generation high-efficiency power devices and have already been commercially utilized. 5) Another promising application using SiC MOSFETs is SiC CMOS ICs.…”
mentioning
confidence: 99%
“…These properties mean SiC crystal has a hardness to radiation and has potential for electronic devices with low soft errors. Operation of 4H-SiC bipolar junction transistors (BJTs), junction field effect transistors (JFETs), and metal-oxide-semiconductor transistors (MOSFETs) have been demonstrated in high temperature environments [4][5][6][7][8][9][10][11][12][13][14]. In terms of the image sensor, 4H-SiC has already demonstrated operation as a UV imaging system with 256 pixels at 400°C [15].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the presence of Nb enhanced the ability to collect the excess carbon atoms released from the SiC substrate during the annealing process, therefore, the Ni/ Nb/n-type 4H-SiC contact exhibited a good ohmic behavior after up to 100 h of aging at 400 °C. 21,22) It seems to be that a thicker thickness of Nb has a better ability to collect the excess carbon atoms, and thus improve the high-temperature reliability. Recently, the dependence of Ni and Nb thickness on low specific contact resistance and high-temperature reliability has been investigated.…”
Section: Introductionmentioning
confidence: 99%